A Pragmatic Alliance : Jewish-Lithuanian political cooperation at the beginning of the 20th century - Staliūnas, Darius; Sirutavičius, Vladas (Book collections on Project MUSE., 2011)
Discusses the political cooperation between Jews and Lithuanians in the Tsarist Empire from the last decades of the 19th century until the early 1920s. These years saw the transformation of both Jewish and Lithuanian political life. Within the Jewish community, the previously dominant integrationists were now challenged both by those who believed that the Jews were not a religious but an ethnic or protonationalist group and those who believed that only with the abolition of capitalism and the establishment of a socialist state would Jewish integration be possible. Among the Lithuanians, the emergence of a modern national identity became increasingly prevalent.